Design and studying the effect of Polepiece shape on the magnetic and optical properties of the unipolar lens - Mohammed. K. A. AL- Janan; R. Y. J. AL-Salih (Tikrit Journal of Pure Science, 2023)
The investigation of a study of each design included the calculation of its axial magnetic field the magnetization of the lens in addition to the magnetic flux density using Finite Element Method (FEM) at three different values of current density (σ = 2,4 and 6 A/mm2). So clearest values and behavior have been obtained at the value current density of (2 A/mm2). It is found that the best magnetizing properties, the highest value of magnetic flux and the lowest value of band width of the axial magnetic field strength have been obtained when the pole head shape length was of (1 mm). The effect of current density on the optical properties has been also studied, and it is found that optical properties have been improved also, and chromatic and spherical aberration values have been decreased significantly. Thus, lens was chosen as the best design among the proposed designs.